Comprensión de la acción y de sus resultados - Lerner Stein, Roberto (1985)
Using an experimental device that served before to study the notion of quotity, the author analyzed the comprehension of the relationship between action and its results. 51 subjects of 5, 6 and 7 years of age were exposed to 7 experimental situations and performances evidenced the existencie of different developmental lines.